The level of grief in women with pregnancy loss: a prospective evaluation of the first three months of perinatal loss - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2021)
Objective: To prospectively investigate perinatal grief in women with pregnancy loss. Methods: A total of 215 women (mean (SD) age: 30.7 (5.9) years) who experienced pregnancy loss were included. Data on sociodemographic, marital and obstetric characteristics and Perinatal Grief Scale (PGS) (first 48 h, 1 week, 1 month and 3 months after the loss) were recorded. Results: Active grief scores were lower (p ranged < .05 to <.01), while difficulty coping (p < .05 for each) and despair (p < .05 for each) scores were higher in the 3rd month as compared with prior assessments. All PGS scores at the 48 h and 3rd month assessments were significantly higher in assisted and planned pregnancies (p < .01 for each). Maternal age was positively correlated with 48 h active grief (r = 0.19, p < .001), despair (r = 0.13, p < .05) and total PGS (r = 0.13, p < .05) scores. Parity and the number of children were negatively correlated (r ranged from -0.35 to -0.20, p < .01 for each) with all PGS scores. Conclusion: Our findings revealed decrease in active grief levels, whereas gradual increase in difficulty coping and despair in women with pregnancy loss within the first 3 months of losing a child. Our finding indicate association of older maternal age, primiparity, assisted and planned pregnancies with regular antenatal follow up with higher total PGS scores as well as active grief, difficulty coping and despair scores in women regardless of the time of assessment within 3 months after the pregnancy loss.
Keywords: Pregnancy loss; grief; women; sociodemographic; obstetric; risk factors; POPULATION; MISCARRIAGE; STILLBIRTH; STRESS; PTSD